Accountability: state cover provided to public officials liable for civil claims against the state - Sutton, Walter (University of the Free State, 2021)
This study explores the meaning and different features of accountability as a constitutional value and obligation within the context of administrative action and how it relates to state cover provided to public officials liable for civil claims against the state. As accountability contributes to the realisation of just administrative action, the requirements for reasonableness and rationality are investigated and applied to decide whether such officials are entitled to state cover. A critical analysis of the criteria applicable to state cover is conducted. The analysis is preceded by a historical overview of how the criteria for state cover were developed before and since the adoption of current legislation and regulations concerned. Once a liability determination is made that an official is liable in law for compensation payments made and forfeits state cover, steps to recover expenditure involved must be initiated. Should an official enjoy state cover, the state as a bearer of its risks will accept all expenditures involved, and a claim against the official must be waived. Based on an investigation conducted to determine current trends with the waiver of claims against officials, it is evident that most claims for compensation payments against officials who are liable in law for such claims and who enjoyed state cover are waived. These trends may compromise accountability as a constitutional obligation. They may indicate due diligence that is lacking when decisions concerning the forfeiture or not of state cover are being made. The study is concluded with an investigation to determine the sufficiency or not of the criteria for state cover to secure accountability as intended by national legislation. Although the current criteria may be sufficient to pass constitutional muster to promote accountability as a constitutional value and obligation, it may not be sufficient to secure it. Recommendations are made to improve the current criteria to secure accountability and to continue with further research.
Dissertation (LL.M. (Constitutional Law and Philosophy of Law))--University of the Free State, 2021
Keywords: Government accountability; Liability (Law); Compensation payments vs state cover